2021
DOI: 10.1096/fj.202100027r
|View full text |Cite
|
Sign up to set email alerts
|

Microbial‐derived indoles inhibit neutrophil myeloperoxidase to diminish bystander tissue damage

Abstract: During episodes of acute inflammation, polymorphonuclear leukocytes (PMNs) are actively recruited to sites of inflammation or injury where they provide anti-microbial and wound-healing functions. One enzyme crucial for fulfilling these functions is myeloperoxidase (MPO), which generates hypochlorous acid from Cl − and hydrogen peroxide. The potential exists, however, that uncontrolled the extracellular generation of hypochlorous acid by MPO can cause bystander tissue damage and inhibit the healing response. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 102 publications
(237 reference statements)
1
22
0
Order By: Relevance
“…Indoles have also been shown to be protective in the context of intestinal inflammation by acting on the innate immune system. For example, indoles, including indole, IPA, and IAA, have been demonstrated to inhibit neutrophil myeloperoxidase (MPO) in assays using both purified, recombinant human MPO and primary human neutrophils [151,152]. MPO, through its generation of hypochlorous acid from hydrogen peroxide, is essential for neutrophil anti-microbial activity but can cause damage to "bystander" tissues during uncontrolled inflammation [153].…”
Section: Protective Actions Of Indolesmentioning
confidence: 99%
“…Indoles have also been shown to be protective in the context of intestinal inflammation by acting on the innate immune system. For example, indoles, including indole, IPA, and IAA, have been demonstrated to inhibit neutrophil myeloperoxidase (MPO) in assays using both purified, recombinant human MPO and primary human neutrophils [151,152]. MPO, through its generation of hypochlorous acid from hydrogen peroxide, is essential for neutrophil anti-microbial activity but can cause damage to "bystander" tissues during uncontrolled inflammation [153].…”
Section: Protective Actions Of Indolesmentioning
confidence: 99%
“…Supplementation of mice during DSS colitis with these compounds revealed that tryptophan metabolites are protective in the context of acute intestinal inflammation, at least in part through AHR-dependent induction of IL-10R1 on epithelial cells. Subsequent studies using bacteria-derived indole compounds found that they specifically inhibit neutrophil myeloperoxidase, a key inflammatory mediator during acute colitis, and suggest that microbial-derived tryptophan metabolites can directly act on innate immune cells to attenuate the inflammatory response [ 137 ].…”
Section: Role Of Microbiota In Modulating Intestinal Barrier and Inflammationmentioning
confidence: 99%
“…In mouse models of IBD, the metabolite indole-3-propionic acid (IPA) dramatically alleviated DSS-mediated intestinal inflammation resulting in restored intestinal tissue architecture and a reduction in inflammatory parameters, such as histologic score and colon shortening [ 136 ]. IPA, exclusively produced from tryptophan by distinct subsets of the gut microbiota, has been implicated in both regulation of innate immune activity and suppression of gut inflammation through synergistic activation of the pregnane X receptor with another microbiota-derived tryptophan metabolite, 1 H -indole [ 137 , 184 , 185 , 186 , 187 ]. IPA also demonstrates potent anti-oxidant activity and shows neuroprotective characteristics in models of neurodegenerative disorders such as Alzheimer’s disease and ischemic stroke [ 188 , 189 ].…”
Section: Approaches To Intervene In Modulating Host–microbe Interactionsmentioning
confidence: 99%
“…Indoles Induction of IL-10 signaling and inhibition of excessive neutrophil myeloperoxidase production [128,129] Tuberonic acid…”
Section: Metabolite Effect Referencementioning
confidence: 99%
“…Enhance epithelial proliferation and barrier integrity. [20,135] Alexeev et al [128,129] reported that microbial-derived indoles assist during epithelial damage and promote tissue healing via the induction of IL-10 signaling and the inhibition of the excessive neutrophil myeloperoxidase production. In the same vein, Sung et al [130] identified another microbial metabolite, the tuberonic acid, that exerts anti-inflammatory properties and has a beneficial role during epithelial tissue repair.…”
Section: Metabolite Effect Referencementioning
confidence: 99%